Colometric Analysis of Paul's Letters - Marschall, Priscille (Mohr Siebeck, 2023)
Am Beispiel von 2. Korinther 10–13 untersucht Priscille Marschall, inwieweit der Stil des Paulus den antiken Konventionen der Gliederung griechischer Prosatexte in »côla« und »Perioden« entspricht. Die Autorin zeigt auch, wie die Berücksichtigung der Kolometrie den Exegeten bei der Behandlung von Fragen der Zeichensetzung helfen kann.InhaltsübersichtIntroduction Chapter 1: Ancient Colometry and the New Testament: Status Quaestionis and Aims of this Study Chapter 2: Côla, Commata, and Periods: The Data from the Rhetorical Treatises Chapter 3: Towards a Method of Colometric Analysis Chapter 4: Essay of a Colometric Analysis of 2 Cor 10–13 Chapter 5: Re-punctuating Paul's Letters in Light of their Colometric Structure Conclusion Priscille Marschall focuses on a hitherto neglected aspect of the study of the elocutio of Paul's letters: colometry, i.e., the way in which ancient authors used to structure their orality-oriented compositions into »côla« (κῶλα) and »periods« (περίοδοι). Based on a thorough study of rhetorical treatises from the Greco-Roman world, the author first develops a set of criteria for delineating the côla and the periods. Using 2 Corinthians 10–13 as a case study, she then examines the extent to which Paul's style complies with the conventions of structuring prose outlined by the ancient rhetoricians. Lastly, she explores the links between colometric structure and punctuation, showing how colometric analysis can inform exegetical debates related to segmentation issues and questioning how we might (re)punctuate Paul's letters in order to render something of their oral logic of structuration.Survey of contentsIntroduction Chapter 1: Ancient Colometry and the New Testament: Status Quaestionis and Aims of this Study Chapter 2: Côla, Commata, and Periods: The Data from the Rhetorical Treatises Chapter 3: Towards a Method of Colometric Analysis Chapter 4: Essay of a Colometric Analysis of 2 Cor 10–13 Chapter 5: Re-punctuating Paul's Letters in Light of their Colometric Structure Conclusion
10.1628/978-3-16-162555-8
Keywords: Hochschulschrift; Feminist Studies; Wissenschaftliche Untersuchungen zum Neuen Testament 2. Reihe; Frame Semantics; Ian McEwan; Hellenistic And Roman Religion; antike politische Philosophie; Canonicity; Jugendamt; Paul's letters; Ancient Rhetoric; Punctuation; stylistic / elocutio; Colometric Analysis; 2 Corinthians 10–13; colometry; orality / aurality; Neues Testament